Deformation interaction of panel residential buildings with the soil in the zone of technogenic impact - Gusev, Georgiy Nikolayevich; Shardakov, Igor’ Nikolayevich; Baryah, Aleksandr Abramovich; Glot, Irina Olegovna (Computational Continuum Mechanics, 2023)
The design, construction and operation of buildings under conditions of technogenic impact caused by mining represents a system of complex and knowledge-intensive tasks. As part of research in this direction, it is required to solve the problems of mathematical modeling of the interaction between the structure and the soil mass in the zone of undermined territories, as well as the problems of verifying the numerical solutions by comparison with the data of monitoring the stress-strain state (SSS) of the "building–foundation–soil mass" systems. Furthermore, the solution of these problems is complicated by a large number of types of building structures, the nature of interaction of which with the soil foundation differs significantly. In addition, the deformation response of the structure itself to the man-made impact caused by mining is different. The paper analyzes the state of building structures, namely, panel residential buildings located in the zone of undermined territories of the Verkhnekamsk potassium salt deposit in the city of Berezniki, Perm Territory. A mathematical model of the SSS of the "building–foundation–soil mass" system is presented. This model describes the possibility of elastic and inelastic deformation of the system elements and the non-ideal contact between the foundation and the soil mass. It also takes into account the elastic-plastic properties of the soil foundation. In the numerical experiment, the multi-parameter dependences of the strain-state state of panel structure elements on the parameters of soil mass surface deformation provoked by technogenic processes during mining were calculated. The obtained dependences make it more reasonable to determine the maximum horizontal deformations of the soil, at which the limiting stress in the elements of the building is reached.